PERANCANGAN APLIKASI PENILAIAN OTOMATIS JAWABAN UJIAN ESAI DENGAN METODE RABIN KARP - Gozal, Wilson (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Automated Essay Grading System With Rabin Karp Method is and application designed to match answer with the answer key of the student essays that have been previously determined. The main process of Rabin Karp answer matching and Semantic Similarity answer matching supported by Tagging process. The result obtained are pretty good, but there are still some things that become lack for program making the final score given less accurate, when there is an answer that uses words that have the same meaning but different words or structures commonly reffered to as synonymous words and word position difference, and the final score that appears are recommended to Key words Automated Essay Matching, Rabin Karp, Semantic Similarity.